2014
DOI: 10.11604/pamj.2014.17.151.3818
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chlamydia trachomatis among patients with acute conjunctivitis in kasr alainy ophthalmology clinic

Abstract: IntroductionTrachoma is a leading cause of avoidable blindness and endemic conjunctivitis in 57 countries. It infects approximately 84 million people globally, and continues to threaten over 10% of the world's population with the risk of blindness.MethodsThis is a cross sectional descriptive study assessing patients presenting with acute conjunctivitis. A full history was taken from patients followed by examination of both eyes. A conjunctival swab was taken and a sample of tears was collected and handled at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This group suggested that IgG levels to CPAF may serve as a biomarker for patients at risk of inflammatory trachoma. More recently Mowafy et al [ 129 ] utilised tear ELISA assays to detect IgG and IgM of patients with trachoma.…”
Section: Tear Fluid Analysis In Ocular Diseasementioning
confidence: 99%
“…This group suggested that IgG levels to CPAF may serve as a biomarker for patients at risk of inflammatory trachoma. More recently Mowafy et al [ 129 ] utilised tear ELISA assays to detect IgG and IgM of patients with trachoma.…”
Section: Tear Fluid Analysis In Ocular Diseasementioning
confidence: 99%
“…In this sense, we consider maternal or prenatal infections of C. trachomatis, which is a member of Chlamydiaceae family, and the chlamydial non-gonococcic urethritis factor, as non-excludable from schizophrenia aetiopathogenesis [88]. It is well known that C. trachomatis is associated with manifestations such as conjunctivitis [89], nasopharyngitis [90], pneumonia [91] and rarely myocarditis [92], encephalitis [93]. An American study conducted in 2001 assessed the contribution of maternal infections during pregnancy to schizophrenia (or the other psychoses) development in adulthood and reported that neonatal HSV-2 seropositivity increased risk.…”
Section: Coherencementioning
confidence: 99%